Evaluation of Validity and Efficiency of Diagnostic Criteria in Autoimmune Hepatitis in Children - Imanieh, Mohammadhadi; Farzaneh, Nazanin Amin; Dehghani, Seyed Mohsen; Shahrebabak, Maryam Gholami; Hosseinabadi, Samaneh Hamzelou (Turkish Journal of Gastroenterology, 2021)
Background: Autoimmune hepatitis (AIH) is a progressive inflammatory liver disease with various clinical symptoms, but treatment andprevention of hepatic failure and cirrhosis is possible with early diagnosis. However, no specific test has been approved for the diagnosisof AIH. In 2008, the International Autoimmune Hepatitis Group (IAIHG) developed a simplified diagnostic scoring system that has beenwidely used in practice. Nevertheless, it cannot distinguish AIH from Primary Sclerosing Cholangitis (PSC) and consensus is lacking withrespect to its validity, sensitivity, and applicability for children patients. The newer 2018 version also requires validation. The presentstudy intends to evaluate the validity and efficiency of the IAIHG simplified scoring system and new scoring system in children with AIH.Methods: The present study is a non-interventional case–control study covering 152 patients with hepatic diseases (83 patients withAIH and 69 patients with Wilson disease (WD)). Titers of autoantibodies, IgG levels, hepatic histology, and absence of viral hepatitis werescored and calculated according to IAIHG diagnostic criteria. Statistics software package (SPSS) and draft receiver operating characteristic(ROC) curves was used to analyze data and determine value of diagnostic criteria.Result: In our study, both scoring systems’ accuracy was good in AIH diagnosis, although new score displays higher sensitivity and specificity,suggestive of greater accuracy and predictive strength.Conclusion: Our study is the first validation study of the new scoring system in diagnosing AIH, and further studies require verifying thisscoring system.